Economic Regionalism as a Planetary Phenomenon. Theory And Methodology of Comparison - Andrey A. Baykov (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2017)
Nowadays integration could be considered as worldwide-political phenomenon with its multielement structure. The growing integratedness allows the little and medium states to build a constructive conversation with important players, equalize the growth rates, life quality as well as to contribute to settlement of international conflicts. This article deals with the theory and methodology of Economic Integration in Europe. The author investigates the roots of integration processes in after-war period in Europe. With establishment of European Coal and Steel Community (ECSC) in 1951 the integration became a key element of international policy. The author revises the evolution of the Integration theory from implementing of “federalism” term till development of comparative integration area in international relations science. The author used original foreign and Russian sources for preparing the current article.